Kebijakan Penataan Kawasan Takssim Bakmie dan Kopi Ditinjau Dari PERMEN PARIWISATA DAN EKONOMI KREATIF NOMOR 4 TAHUN 2021 - Khadry, Muhammad; Sheila Vanessa, Wella Bella May (Politeknik Pariwisata Medan, 2024)
Significant developments in the Indonesian economy can be attributed to its tourism sector, as stated by Santosa (2011:34). In recent years, Barreto and Giantari (2015:34) have observed the growth of the Indonesian tourism industry. According to Law Number 10 of 2009 concerning Tourism, this sector includes various activities supported by facilities and services provided by individuals, companies, government agencies, and local governments. Certain tourist destinations are promoted, managed, and developed by tourism business actors to increase regional economic income through visitor attraction. This business was created to support tourism growth. The goal is to attract tourists by carrying out activities that meet their needs. Meanwhile, based on Law Number 10 of 2009 concerning Tourism, it states that Tourism Business is a business that provides goods and/or services to meet the needs of tourists and organize tourism.